(untitled) (LACCEI, 2024)
Abstract– The United Nations organization affirms that empowerment is necessary for equality and development it establishes it as a sustainable development objective. The purpose of the study was to determine the evidence of validity and reliability of the questionnaire for measuring empowerment among women in the province. The study population was made up of women between 15 and 50 years of age in the province of Trujillo. The calculation of Aiken’s V coefficient was used to demonstrate the validity of content, to review the internal structure, the factor analysis method was used, finding a new factor structure of 7 dimensions and 2 items that did not meet an adequate factor weight were removed, establishing a total of 42 items in the instrument, which explain 60% of the variance.